Odkrywanie Znanieckiego. O niezrealizowanej recepcji Floriana Znanieckiego = Discovery of Znaniecki. Unfulfilled reception of Florian Znaniecki`s works - Kuszyk-Bytniewska, Mariola (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The discovery of Florian Znaniecki`s oeuvre is like the discovery of America: when you think you know something, you realize that it is less then you knew before. A synthesis of Znaniecki`s legacy is still a challenge. Are Znaniecki`s ideas up to date? Is there anything intriguing for contemporary sensibility?
Keywords: Znaniecki, Florian (1882-1958)